Analysis of ballistic capture in Sun–planet models. Issue 6 (15th September 2015) - Luo, Z.-F.; Topputo, F.
Highlights: To assess the role played by the dynamical model and planetary eccentricity in the ballistic capture about a planet. To study the effect of planet true anomaly, in a quantitative and qualitative way. To evaluate the effect of spatial distribution on ballistic capture orbits. Abstract: Analysis of ballistic capture orbits in Sun–planet systems is conducted in this paper. This mechanism utilizes purely gravitational forces, and may occur in non-Keplerian regimes. Ballistic capture orbits are generated by proper manipulation of sets of initial conditions that satisfy a simple definition of stability. Six Sun–planet systems are considered, including the inner planets, Jupiter, and Saturn. The role of planets orbital eccentricity, their true anomaly, and mass ratios is investigated. Moreover, the influence of the post-capture orbit in terms of inclination and orientation is also assessed. Analyses are performed from qualitative and quantitative perspective. The quality of capture orbits is measured by means of the stability index, whereas the capture ratio gives information on their statistical occurrence. Some underlying principles on the selection of the dynamical model, the initial true anomaly, and inclination are obtained. These provide a reference for practical cases.